Analisis Ketahanan Keluarga pada Pasangan Pekerja Pabrik: Perspektif Sosiologi Hukum dan Hukum Islam: Studi Kasus di Kelurahan Asemrowo, Kecamatan Asemrowo, Kota Surabaya - Widodo, Purwo (Program Studi Hukum Ekonomi Syariah, 2024)
Family welfare is everyone's dream. It is undeniable that economic factors are one of the things that greatly determine the welfare of a household. The family economy is no longer the responsibility of men (husbands), but women (wifes) have now taken part in the implementation of meeting daily needs. The reality that occurs in the people of Surabaya, there are married couples who still do not have enough to meet the needs of their families, where the couple both work in factories. This paper focuses on two studies, first, how the concept of family resilience in factory worker couples in the community of Asemrowo Village, Asemrowo District, Surabaya City. Second, what is the perspective of legal sociology and the perspective of Islamic law on family resilience in the factory worker couple. The type of research in this paper is field research, which is classified as qualitative and descriptive. The procedure is to produce descriptive data in the form of written or oral data from respondents and observable community behavior. This study concludes, first, that family resilience in working spouses is measured based on the resources they have, including three aspects, namely physical, psychological, and social. Second, the sociological view of law on family resilience in factory worker couples is an effort to understand family harmony and harmony in terms of social behavior of the community.